2021
DOI: 10.14202/vetworld.2021.3194-3199
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Brix refractometer to estimate immunoglobulin G concentration in goat colostrum

Abstract: Background and Aim: Immunoglobulin G (IgG) concentration is high in goat colostrum, particularly in the first few hours after parturition, and this is important for the kid's immunity and growth. IgG levels vary depending on several factors, including breed, disease status, colostrum management, handling, and collection time postpartum. A handheld optical refractometer, an affordable instrument that is simple to use in the field, is used widely in dairy farms to measure total solids. However, it can also be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…On day 2 and 3 postpartum, IgG values were reduced to 22.4 and 8.4 mg/mL, respectively, in agreement with other published results [ 10 ]. A significant reduction in IgG in goat colostrum during postpartum was observed, similar to that previously described using a colostrometer [ 10 ]. Our study demonstrates that not all the goats have enough IgG content after parturition, as about 10% of the animals in the present study showed values below the optimal threshold, set over 20 mg/mL according to previous studies [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…On day 2 and 3 postpartum, IgG values were reduced to 22.4 and 8.4 mg/mL, respectively, in agreement with other published results [ 10 ]. A significant reduction in IgG in goat colostrum during postpartum was observed, similar to that previously described using a colostrometer [ 10 ]. Our study demonstrates that not all the goats have enough IgG content after parturition, as about 10% of the animals in the present study showed values below the optimal threshold, set over 20 mg/mL according to previous studies [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present trial, the average concentrations of IgG in goat colostrum measured by ELISA on day 1 post-kidding reached 36.6 mg/ml, being lower than those described in some of the previous studies (50.0 mg/mL [ 18 ], 54.4 mg/mL [ 9 ] or 73.67 mg/mL [ 11 ]), but higher than others (10.6 mg/mL [ 10 ]). On day 2 and 3 postpartum, IgG values were reduced to 22.4 and 8.4 mg/mL, respectively, in agreement with other published results [ 10 ]. A significant reduction in IgG in goat colostrum during postpartum was observed, similar to that previously described using a colostrometer [ 10 ].…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations